Bactericidal activity of nano silver against pathogenic microorganisms which cause pecular diseases of genital secretion track - Dung, Tran Thi Ngoc; Hung, Nguyen Duc; Buu, Ngo Quoc; Hung, Le Van; Dung, Nguyen Dang (Vietnam Journal of Science and Technology, 2019)
Nano silver was known as a bactericidal agent for almost all bacterial species and has been intensively investigated over the world to apply for disinfection in different fields of human activities and environmental protection. Specifically, genital exudate media contain numerous dangerous bacteria such as Neisseria gonorrhoeae, Enterococcus faecalis, Staphylococcus aureus, Candida albicans etc. which as a rule are drug-resistant with respect to antibiotics. This research presents the results of the application of nanosilver in replacing antibiotics in elimination of the above mentioned microorganisms by using low nanosilver concentrations of about 0.01 mg/cm2 immobilized on non-woven fabric. The experimental data showed that nanosilver-impregnated fabric samples at a concentration 0.01 mg/cm2 gave antibacterial rings of 10 mm, 9 mm and 8 mm, respectively, for N. gonorrhoeae, Candida albicans + E.coli and Candida albicans + E.coli + S. aureus.